PENGARUH PENGAWASAN TERHADAP PENINGKATAN PRODUKTIVITAS KERJA PEGAWAI PADA YAYASAN AT-TAQWA GUMAWANG BELITANG OKU TIMUR - Alfarabi, Faisal; Apriyanti, Rini (Jurnal Trisna Riset, 2025)
Skilled human resources are an important component in government goals. Nowadays there are more and more companies or institutions that have good human resources and services, one of which is the At-Taqwa Gumawang Belitang OKU East Foundation. The At-Taqwa Foundation operates in the fields of social, religious, educational and health services to the community. In essence, in an organization or company, the issue of supervision is a very complex matter and the most important thing to do is to increase the productivity achieved by employees, especially at the At-Taqwa Gumawang Belitang OKU East Foundation. The problem faced by the At-Taqwa Gumawang Belitang OKU East Foundation is that management does not have enough time to carry out effective supervision so that supervision is less than optimal. This research aims to find out how supervision affects employee work productivity at the At-Taqwa Gumawang Belitang OKU East Foundation. Effective supervision is expected to improve employee performance, which in turn will have a positive impact on organizational productivity. The method used in this research is a quantitative approach by collecting data through questionnaires distributed to foundation employees. The research method used is quantitative analysis using the correlation coefficient formula. Based on the results of the analysis in the research, supervision has a low influence on employee work productivity. It is hoped that this research can provide recommendations for foundation management in improving the monitoring system to achieve better performance. The advice given is that the East OKU At-Taqwa Gumawang Belitang Foundation should pay more attention to the condition of its employees, so that they are motivated to work harder so that the desired increase in work productivity is achieved.